Ivan Karamazov’s rebellion in Albert Camus’ and Karl Jaspers’ interpretations - Lisowska, Urszula (Journal of Education Culture and Society, 2020)
The aim of this study is to present Albert Camus’and Karl Jaspers’ interpretations of Ivan Karamazov’s rebellion as the diagnoses of the weakness of the human intellect in confrontation with the world and the criticism of rationalism. Therefore, in the introduction I will present those fragments of the novel that characterize Ivan’s rebellion as highly abstract and theoretical. At the same time, this common literary context serves as the ground for reconstruction and comparison of the basic philosophical assumptions of each author. The intention of the remaining part of the paper is, firstly, to reconstruct A. Camus’ and K. Jaspers’epistemology and, secondly, to analyse the arguments against Ivan’s attitude formulated by the writers. Their criticisms of the protagonist’s excessive trust in intellect is based on their own concepts of human epistemic capacity, which are related to the problems of the absurd in A. Camus’ and transcendence in K. Jaspers’ writings. The question of nihilism demands analysis of A. Camus’ idea of the nature of rebellion as both affirmative and negative, and of K. Jaspers’ notion of faith as pre-intellectual trust. Finally, their criticisms of the slogan “If there is no God, then anything is allowed” introduces the problem of freedom, which allows the comparison of the concepts of solidarity (A. Camus) and communication (K. Jaspers). In the conclusion these two philosophical attitudes are discussed together.